Місцеве самоврядування в Україні та державах-учасницях ЄС: конституційне регулювання й організаційні моделі - Соколов, Сергій Олександрович (Київський національний університет імені Тараса Шевченка, 2025)
Досліджено теоретико-правові засади місцевого самоврядування як конституційного інституту, а також проведено порівняльний аналіз його основних організаційних моделей. Проаналізовано конституційно-правове регулювання місцевого самоврядування в Україні у порівнянні з гарантіями у Франції, Німеччині та Польщі, ідентифіковано системні прогалини. Проведено комплексну оцінку чинної української моделі, яка визначена як операційно ефективна, але конституційно крихка, вразлива до фінансової рецентралізації та неправомірного державного втручання. Обґрунтовано необхідність та розроблено концепцію «Конституційного Пакету» для адаптації універсальних європейських механізмів. Сформульовано пропозиції щодо конституційного закріплення принципу Konnexität з механізмом судового контролю через КСУ, запровадження інституту Префекта з повноваженнями, суворо обмеженими контролем законності та судовим пріоритетом. Також обґрунтовано необхідність конституційного закріплення Gebietsgarantie для нового АТУ, функціонального розмежування повноважень між рівнями, посилення механізмів прямої демократії та інтеграції гарантій кризової стійкості і захисту професійного корпусу муніципальних службовців.

The theoretical and legal foundations of localself-government as a constitutional institution are investigated, alongside a comparative analysis of its main organizational models (Anglo-Saxon, Continental, German, and Polish). The constitutional regulation of local self-government in Ukraine (Section XI of the Constitution) is analyzed in comparison with the guarantees in France, Germany, and Poland, identifying systemic deficiencies. A comprehensive assessment of the current Ukrainian model concluded that it is operationally effective but constitutionally fragile, vulnerable to financial recentralization and unauthorized state interference. The necessity of adopting a comprehensive "Constitutional Package" for adapting universal European mechanisms has been substantiated. Proposals have been formulated regarding the constitutional entrenchment of the Konnexität principle (financial compensation for mandates) with a judicial review mechanism via the Constitutional Court, and the introduction of the Prefect institution with powers strictly limited to legality control and judicial priority. The research also substantiates the need for constitutional guarantees of Gebietsgarantie (territorial stability) for the new Administrative-Territorial Arrangement (ATA), functional demarcation of powers between levels, strengthening direct democracy mechanisms, and integrating crisis resilience (continuity of government) guarantees and the protection of the professional municipal civil service corps.
Local self-government in Ukraine and EU Member States: constitutional regulation and organizational models
Keywords: місцеве самоврядування; конституційне регулювання; децентралізація; Європейська хартія; Konnexität; Префект; державний нагляд; Gebietsgarantie; організаційні моделі; кризова стійкість; local self-government; constitutional regulation; decentralization; European Charter; Konnexität; Prefect; state supervision; Gebietsgarantie; organizational models; crisis resilience